2020
DOI: 10.1037/bul0000296
|View full text |Cite
|
Sign up to set email alerts
|

Reward-driven distraction: A meta-analysis.

Abstract: People have a strong tendency to attend to reward cues, even if these cues are irrelevant to their current goal or their current task. When reward cues are goal-irrelevant, their presence may impair cognitive performance. In this meta-analysis, we quantitatively examined the rapidly growing literature on the impact of reward-related distractors on cognitive performance. We included 91 studies (N = 2,362) that used different cognitive paradigms (e.g., visual search, conflict processing) and reward-related stimu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 188 publications
(360 reference statements)
6
41
0
Order By: Relevance
“…Cues become important in part because of their past association with rewards. Research has shown that stimuli that were rewarding in the past attract attention even when irrelevant to a current task (Rusz et al., 2020). For example, when colored shapes in an online task had previously been associated with rewards, the shapes continued to attract participants’ attention despite being irrelevant to what they were currently doing (Anderson, 2016).…”
Section: Forming Habits: Rewards For Social Media Usementioning
confidence: 99%
“…Cues become important in part because of their past association with rewards. Research has shown that stimuli that were rewarding in the past attract attention even when irrelevant to a current task (Rusz et al., 2020). For example, when colored shapes in an online task had previously been associated with rewards, the shapes continued to attract participants’ attention despite being irrelevant to what they were currently doing (Anderson, 2016).…”
Section: Forming Habits: Rewards For Social Media Usementioning
confidence: 99%
“…There now is converging empirical evidence that attention can be captured automatically by non-salient and task-irrelevant stimuli if these stimuli are associated with either reward or punishment (Anderson 2015;Anderson & Kim, 2018;Anderson, Laurent & Yantis, 2011a, 2011bAnderson & Yantis, 2012;Gluth et al, 2020;Le Pelley et al, 2016;Rusz et al, 2020;Schmidt, Belopolsky, & Theeuwes, 2015a, 2015bWang, Yu, & Zhou, 2013;Wentura, Mueller, & Rothermund, 2014). Most of these experiments have concluded that the potential of an irrelevant distractor to capture attention is linked to the strength of its association with reward.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research indicates that prior experience can exert varied effects on attentional prioritisation of visual stimuli. Specifically, it has been shown learning about the value of rewards and punishments associated with a stimulus can increase the priority of that stimulus (for reviews, see Anderson, 2016;Le Pelley et al, 2016;Rusz et al, 2020;. A second stream of research has shown that statistical learning can result in attentional suppression of locations in which salient distractor stimuli are likely to appear (e.g., Failing, Feldmann-Wüstefeld, et al, 2019;Wang et al, 2019;Wang & Theeuwes, 2018a, 2018b.…”
Section: Discussionmentioning
confidence: 99%
“…One example of this influence of prior experience on attention is seen in a recent body of work demonstrating that the likelihood that a stimulus will receive attentional priority is modulated by previous learning about the relationship between that stimulus and events of motivational significance: rewards and punishments (for reviews, see Anderson, 2016;Le Pelley et al, 2016;Rusz et al, 2020;. This effect has been demonstrated across a range of procedures; here we focus on a procedure developed by Le Pelley, Pearson, Griffiths and Beesley (2015;see also Watson, Pearson, Most, et al, 2019), which was a variant of the additional singleton task (Theeuwes, 1992).…”
Section: Introductionmentioning
confidence: 99%